2020
DOI: 10.1039/d0ra04255b
|View full text |Cite
|
Sign up to set email alerts
|

Direct sulfonamidation of (hetero)aromatic C–H bonds with sulfonyl azides: a novel and efficient route toN-(hetero)aryl sulfonamides

Abstract: N-Aryl sulfonamides belong to a highly important class of organosulfur compounds which are found in a number of FDA-approved drugs such as dofetilide, dronedarone, ibutilide, sotalol, sulfadiazine, sulfamethizole, vemurafenib, and many more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 89 publications
0
18
0
Order By: Relevance
“…Finally, it should be noted that transition metal complexes play important roles in intermolecular 1,2-difunctionalization of alkenes and the synthesis of organic compounds. [32][33][34][35][36][37][38][39][40]…”
Section: Chloro-trifluoromethylthiolationmentioning
confidence: 99%
“…Finally, it should be noted that transition metal complexes play important roles in intermolecular 1,2-difunctionalization of alkenes and the synthesis of organic compounds. [32][33][34][35][36][37][38][39][40]…”
Section: Chloro-trifluoromethylthiolationmentioning
confidence: 99%
“…11 However, synthesis of b-halovinyl sulfones through the direct halosulfonylation of simple and easily accessible alkynes was almost omitted, while this procedure has recently attracted a lot of attention because of its operational simplicity and high atom and step economy. In connection with our recent reviews on the synthesis of organosulfur compounds 12 and new methodologies in modern organic synthesis, [13][14][15][16][17][18][19][20] herein, we provide an overview of the direct halosulfonylation of C-C triple bonds (Fig. 1), with special emphasize on the mechanistic aspect of the reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In light of the increasing interest on this chemistry, we concluded that it was timely to summarize the available literature on this domain in a comprehensive review paper. In continuation of our preceding works on organosulfur chemistry 19 and modern organic synthesis, [20][21][22][23][24][25][26] we summarize here the most important contributions toward the synthesis of N-sulfenyl-, sulnyl-, and sulfonylamines through the controllable oxidative coupling of Fig. 1 General structure of sulfenamides (I), sulfinamides (II), sulfonamides (III), and some related compounds.…”
Section: Introductionmentioning
confidence: 99%